Osteosarcoma without prior retinoblastoma related to RB1 low‐penetrance germline pathogenic variants: A novel type of RB1‐related hereditary predisposition syndrome?. Issue 12 (30th September 2019) - Imbert‐Bouteille, Marion; Gauthier‐Villars, Marion; Leroux, Dominique; Meunier, Isabelle; Aerts, Isabelle; Lumbroso‐Le Rouic, Livia; Lejeune, Sophie; Delnatte, Capucine; Abadie, Caroline; Pujol, Pascal; Houdayer, Claude; Corsini, Carole
Abstract: Background: Retinoblastoma (Rb) is a rare intraocular malignant tumor in children with high overall survival. Predisposition to Rb is linked to RB1 germline mutations with high penetrance, but rare RB1 low‐penetrance variants are also known. Rb survivors are at risk of second primary malignancies (SPMs), mostly osteosarcoma and soft‐tissue sarcoma. Nevertheless, the risk of primary osteosarcoma developing without prior Rb has not been reported in RB1 germline mutation carriers. Methods: We report a patient in whom osteosarcoma developed at age 17 as a first primary malignancy within a family context of sarcoma. Results: Unexpectedly, genetic testing identified a low‐penetrance germline mutation in RB1 [NM_000321.2: c.45_76dup; p.(Pro26Leufs*50)]. In eight additional similar cases from published and unpublished reports of families, first primary osteosarcomas and sarcomas mostly developed in RB1 low‐penetrance mutation carriers without prior Rb. Conclusion: We propose that first primary sarcoma and osteosarcoma could be a novel clinical presentation of a RB1 ‐related hereditary predisposition syndrome linked to RB1 low‐penetrance germline mutations. In these families, careful screening of primary non‐Rb cancer and SPMs is required by maintaining enhanced clinical vigilance. Implementing lifelong periodic whole‐body MRI screening might be a complementary strategy for unaffected carrier relatives in these families. Abstract : The risk of primary osteosarcoma developing without prior retinoblastoma has not been reported in RB1 germline mutation carriers. We report a patient in whom osteosarcoma developed at age 17 as a first primary malignancy within a family context of sarcoma. Unexpectedly, genetic testing identified a low‐penetrance germline mutation in RB1 [NM_000321.2: c.45_76dup, p.(Pro26Leufs*50)]. We propose that first primary sarcoma and osteosarcoma could be a novel clinical presentation of a RB1‐related hereditary predisposition syndrome linked to RB1 low‐penetrance germline mutations and discuss the screening strategy to implement for unaffected carrier relatives in these families.